2003
DOI: 10.1103/physrevb.68.125201
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of carbon interstitials in silicon carbide: A theoretical study

Abstract: Ab initio supercell calculations have been carried out to investigate clusters of carbon interstitials in 3C-and 4H-SiC. Based on the calculated formation energies, the complex formation of carbon interstitials or their aggregation to carbon antisites is energetically favored in SiC. The electronic and vibronic properties of the carbon interstitials and their aggregates depends strongly on the polytype. Using the calculated hyperfine constants and local vibrational modes of carbon clusters the possible relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 45 publications
(56 reference statements)
7
143
1
Order By: Relevance
“…We have recently learned that A. Gali et al calculated the LVMs of the kk-configuration, finding results similar to the 3C-SiC values, and speculated that this defect was the D II center. 21 As the kk-configuration has a 3C-like environment (in contrast to the kh-configuration), the similarity to 3C-SiC is quite natural. However, the conjecture that the ((C 7 In addition, as we noted above, a comparison of the spectra in 3C, 2 4H and 6H-SiC 7 indicates that more than five LVMs may be present also in 3C-SiC.…”
Section: Clustering Of Carbon Atomsmentioning
confidence: 99%
“…We have recently learned that A. Gali et al calculated the LVMs of the kk-configuration, finding results similar to the 3C-SiC values, and speculated that this defect was the D II center. 21 As the kk-configuration has a 3C-like environment (in contrast to the kh-configuration), the similarity to 3C-SiC is quite natural. However, the conjecture that the ((C 7 In addition, as we noted above, a comparison of the spectra in 3C, 2 4H and 6H-SiC 7 indicates that more than five LVMs may be present also in 3C-SiC.…”
Section: Clustering Of Carbon Atomsmentioning
confidence: 99%
“…60 Previous ab-initio studies on aggregation of C I have demonstrated that C I can be trapped by C Si and form stable carbon clusters with the configuration of di-carbon antisite. [61][62][63] Though there has been no evidence showing that Si I can be captured by antisites or C I can aggregate at Si C , we assume that interstitials can form defect clusters with antisite defects with a capture distance of 2NN. The resulting clusters are also referred as interstitial clusters in this study.…”
Section: Clustering Between Point Defects and The Growth And The Shrimentioning
confidence: 99%
“…Earlier work on SiC has shown that the value = 0.20 reproduces the band gap of different polytypes very well, 38 so in the case of SiC this value was used. 57,55…”
mentioning
confidence: 99%